CRISC certified in risk and information systems control all-in-one exam guide - Gregory, Peter; Rogers, Bobby E.; Dunkerley, Dawn (McGraw-Hill Education, 2022)
A fully updated self-study guide for the industry-standard information technology risk certification, CRISC Written by information security risk experts, this complete self-study system is designed to help you prepare for--and pass--ISACA's CRISC certification exam. CRISC Certified in Risk and Information Systems Control All-in-One Exam Guide, Second Edition features learning objectives, explanations, exam tips, and hundreds of practice questions. Beyond exam prep, this practical guide serves as an ideal on-the-job reference for risk management and IT security professionals. Covers all exam topics, including: IT and cybersecurity governance Enterprise risk management and risk treatment IT risk assessments and risk analysis Controls and control frameworks Third-party risk management Risk metrics, KRIs, KCIs, and KPIs Enterprise architecture IT operations management Business impact analysis Business continuity and disaster recovery planning Data privacy Online content includes: 300 practice exam questions Test engine that provides full-length practice exams and customizable quizzes by exam topic.